A MULTILEVEL MODEL OF DYNAMICS OF THE LITHOSPHERE - Zverev A.T. (My University, 1989)
The lithosphere is evolving under the influence of the two global geodynamic 'systems', namely cooling and heating. The first of these induces contraction, causing a general subsidence of the lithosphere. Crustal denudation only decreases the amplitude of subsidence, but does not induce uplift, since the density of the mantle material compensating for the denudation is significantly higher than the density of the sialic masses that are removed. The cooling effect shows up most fully on the continental and oceanic plates. The global geodynamic heating system has a multilevel structure. Its lowest level is located at depths of 2700 to 2900 km, where the abrupt decrease in mechanical competence suggests the presence of an asthenosphere. Heat and mass transport from the bottom of the mantle leads to the development of a second asthenosphere at depths of 700 to 900 km and creates there large-scale horizontal density heterogeneities that are responsible for large positive anomalies of the geoid and low-harmonic isostatic anomalies. In the upper mantle, a third, thick asthenosphere is formed under the influence of heat and mass transport from the middle mantle. Large volumes of basaltic magma are produced and are pumped into the earth's crust. Thermally-induced expansion of the global system of mantle-activated rifts produces compressive stresses in the surrounding upper mantle and crust. The stresses are localized in mobile (weak) zones and result in the compression of these zones and the pileup of mantle-crust matter therein. Two global, oppositely directed outflows (squeeze-out) of matter occur in the top shell of the planet. These are flows from spreading zones (depths of 0 to 400 km) to subduction (or collision) zones, and flows from subduction zones to spreading zones (at depths of 700 to 900 km). The geodynamic spreading-subduction system creates conditions of compression within all of the consolidated crust. This causes deformation, with maximum intensities within zones of stress concentration. The compression generally increases toward collision and subduction zones.